DEVELOPMENT AND ACCEPTANCE OF VISUAL LEARNING MATERIALS FOR STRUGGLING READERS IN SECONDARY SCHOOL - Cadungog, Vanessa (International Journal of Arts, Sciences and Education, 2025)
This study focuses on the development and acceptance of visual learning materials for secondary students struggling with reading, particularly at KNCHS. The study employed a qualitative research design, specifically the participatory rapid appraisal approach. It was conducted at KNCHS-JHS, located in Koronadal City, South Cotabato Province. Through the use of checklists and interviews, significant data were gathered. Based on the study's findings, the developed visual learning material for struggling readers underwent validation by experts in Filipino and ICT, as well as acceptability testing among teachers and students. The study's output, a visual learning material, can be utilized in teaching students with reading difficulties.